PENGARUH OPINI AUDIT TAHUN SEBELUMNYA, KARAKTERISTIK KOMITE AUDIT DAN AUDIT TENURE TERHADAP OPINI AUDIT GOING CONCERN - NADYA PARAMITHA, DEVITA; VENUSITA, LINTANG (Jurnal Akuntansi AKUNESA, 2019)
Going concern problem of the company which results in the companys doubt in maintaining the continuity of its business in the future. This makes the need for research that aims to determine the effect of prior year audit opinion, audit committee characteristics and audit tenure on going concern audit opinion on the mining industry companies registered in the Indonesian Stock Exchange (IDX) in 2013 to 2017. Samples in this study are all of the mining industry companies registered (BEI) in 2013 to 2017 using purposive sampling obtained 155 companies that match the sampling criteria. Research carried out using logistic regression data analysis techniques with SPSS 23 test equipment which obtained the results of the research prior year audit opinion has a positive effect on the probability of going concern audit opinion, audit committee characteristics and audit tenure has no effect on the probability of going concern audit opinion.Keywords:Going-Concern Audit Opinion, Prior Year Audit Opinion, Audit Committee Characteristics and Audit Tenure